Calculation of Shear-Bearing Capacity of Aluminum Alloy-Concrete Composite Beam - Chenghua Li; Ziliang Lu (Buildings, 2025)
This study investigates the shear bearing capacity of aluminum alloy–concrete composite beams to address the limitations caused by the low elastic modulus of aluminum alloys. A finite element model was developed using the Concrete Damaged Plasticity (CDP) model for concrete and validated through parametric analysis. Key factors such as concrete strength, stirrup spacing, and cross-sectional dimensions were examined. An improved shear capacity formula was derived based on the tension–compression bar model and the superposition method. The proposed formula achieved an average ratio of 1.018 to finite element results, with a standard deviation of 0.151, and the proposed formula was validated against 22 FEA models, demonstrating excellent agreement with numerical results and confirming its reliability for practical engineering applications. This work provides a practical analytical approach for the shear design of aluminum–concrete composite structures.